Pengaruh Pelatihan Dan Pengembangan Sumber Daya Manusia Terhadap Peningkatan Etos Kerja Islami Karyawan Bank Syariah Bukopin Cabang Darmo Surabaya - Rahayu, Fujia; Cahyono, Hendry (Universitas Negeri Surabaya, 2018)
The quality of human resources could be reflected by how big the Islamic work ethic level. In this context the training and human resources development is one of tools to improving the human resources quality which owned by the shariah banking industry.This research aims to knowing the influence of training and human resources development to increase the Islamic work ethic of shariah bukopin bank employees branch darmo Surabaya. This research is associative with quantitative approach. The technique of data analysis is using path analysis that used to know how much this contribution of training and human resources development to Islamic work ethic. The result of this research indicate that the training has a significant effect to Islamic work ethic, the development has no significant effect to Islamic work ethic, and the training and human resources development have a significant effect to Islamic work ethic.